Reproduction Traits and Strategies of Two Sardinella Species off the Southwest Coast of Africa - Domingas Perpétua André Quiatuhanga; Pedro Morais; Lilian Anne Krug; Maria Alexandra Teodósio (Fishes, 2025)
Small pelagic fishes such as Sardinella aurita (Valenciennes, 1847) and Sardinella maderensis (R. T. Lowe, 1838) are key intermediate-level components of the marine food web of the southwestern African coast. Their biomass off Angola has shown significant interannual variability, and information about their reproduction is insufficient in the region for adequate stock management. Thus, we aimed to unveil the reproduction period and reproductive traits of these two Sardinella species and establish a link with the prevailing ocean temperature conditions. Adult fish samples were obtained monthly from artisanal and semi-industrial fleets, and the ichthyoplankton samples were collected with a Hydro-Bios Multinet off southwest Angola by Instituto Nacional de Investigação Pesqueira (Angola). The macroscopic inspection of gonads showed that females of both species were more abundant than males. The gonadosomatic index and maturity stages indicate that S. aurita spawns during the Austral summer (December through March), while S. maderensis has a longer spawning period, from October to April. The spawning peak occurs in February for S. aurita and S. maderensis. The mean monthly condition factor of both species was high before and after spawning seasons. The females of S. aurita reach sexual maturity at a smaller size than males, and 50% of the population reaches sexual maturity at a total length of 31.3 cm. The males of S. maderensis reach sexual maturity at a smaller size than females, and 50% of the population reaches sexual maturity at a total length of 28.4 cm. We also found that both species use the southern coast of Angola as a spawning area during the Austral summer and avoid the area during periods of intense upwelling. Currently, these species are managed as a single unit, and the minimum capture size is set at 22 cm, well below the size at sexual maturity registered in the study area. Therefore, we strongly recommend increasing the minimum capture size to guarantee long-term stock viability.